Associations Between Emotion Regulation and Life Satisfaction Among University Students From Germany, Hong Kong, and Japan: The Mediating Role of Social Support - Schunk, Fabian; Trommsdorff, Gisela; Wong, Natalie; Nakao, Gen (Frontiers in Psychology, 2021)
The social adaptiveness of emotion regulation (ER) may differ across cultures due to different social values for the experience and expression of emotions. Specifically, suppression might disrupt social interactions among Germans, but not among Hong Kong Chinese (HKC) and Japanese, due to an emphasis on self-expression and authenticity in Western cultures. In the present study, we examined cultural differences in associations of ER strategies with life satisfaction and social support. Extending prior research, we also test whether social support functions as a mediator for relationships between ER strategies and life satisfaction within cultural groups. University students from Germany (N = 148), Hong Kong (N = 125), and Japan (N = 127) participated in our online survey. Moderation analyses revealed that suppression was related to lower life satisfaction and less social support among Germans, but not among HKC nor Japanese. Social support completely mediated the negative relationship between suppression and life satisfaction among Germans. Furthermore, for Germans and HKC, social support partially mediated the positive relationship between reappraisal and life satisfaction, and the negative relationship between rumination and life satisfaction. Our findings suggest that cultural differences in the associations between ER and well-being might be largely explained by the differential effect of ER strategies on social functioning and adaptation in the respective cultural context.